Parametric Modeling of RV Reducer and Realization of 3D Printing Rapid Prototyping - Xiaxi Li; Jiankun Cui (Jixie chuandong)
Abstract RV reducer is the core transmission component of industrial robots. It is a new type of transmission device suitable for high-precision transmission developed on the basis of conventional cycloidal pinwheel and planetary gear transmission. Taking the RV reducer parts design as the research object, the transmission principle and system composition of RV reducer are introduced, the parametric equation of standard cycloidal gear is expounded, and the parametric modeling method of cycloidal pinwheel based on Autodesk Inventor software platform is mainly discussed. In view of the three-dimensional model of the virtual prototype of RV reducer, the physical model is made by the rapid prototyping technology of light curing. The dimension and surface accuracy of the parts are high, which provides a feasible help for the following demonstration of the overall structure and the research and development of important parts and components.